Measuring the micromechanical properties of oesophageal mucosa with atomic force microscopy. Issue 4 (16th December 2020) - Lin, Chengxiong; Xie, Jingyang; Li, Wei
Abstract : The micromechanical properties of soft tissue can be used as markers for the physiological state and function of the tissue. Deep understanding of the micromechanics of soft tissue, such as the oesophagus, is of great significance to the design of artificial oesophagi, endoscope materials and coatings for medical devices. Here, the micromechanical properties of oesophageal mucosa were studied under different loading rates, deflections, and dwell time by using atomic force microscopy. The micromechanical properties of soft tissue included elastic modulus, plasticity and adhesion force. Results showed that the micromechanical properties changed with increasing loading rate, deflection and dwell time. The micromechanical properties of oesophageal mucosa were related to time‐dependent behaviours, such as contact stress, energy transformation, and strain gradient plasticity. Furthermore, the heterogeneity of oesophageal mucosa affected the micromechanical properties. The force mapping mode was a reliable and effective means to study the micromechanical properties of soft tissue. The results can provide a basis and technical support for the diagnosis of oesophageal diseases from a microscale as well as a material design perspective.